An evaluation of multiple‐schedule variations to reduce high‐rate requests in the picture exchange communication system. Issue 2 (27th January 2016) - Landa, Robin; Hanley, Gregory P.
Abstract : Using procedures similar to those of Tiger, Hanley, and Heal (2006), we compared two multiple‐schedule variations (S+/S– and S+ only) to treat high‐rate requests for edible items in the Picture Exchange Communication System (PECS). Two individuals with autism participated, after they showed persistent requests for edible items after PECS training. Stimulus control was achieved only with the multiple schedule that involved presentation of a discriminative stimulus during reinforcement components and its removal during extinction components (S+ only). Discriminated requests were maintained for the 1 participant who experienced schedule thinning.